(untitled) (Andamios, Revista de Investigación Social, 2007)
Many scholars have pointed out that the work of Max Weber supposes a permanent confrontation with classical Marxism. Elaborating on this idea, this paper’s goal is to review and critically appraise the epistemological and methodological discussion Weber takes on with historical materialism in his essay Cognitive “objectivity” of social science and policy. The “monist” tendency in causal explanation, on the one hand, and the ignorance of the “fictional”, “typical-ideal” or “instrumental” character of its laws and concepts and, on the other, are the two pillars on which Weber builds up his criticism.